PENGARUH KEPEMIMPINAN DAN KOMUNIKASI TERHADAP KINERJA APARATUR SIPIL NEGARA (ASN) PADA SEKSI WILAYAH 1 BALAI PENGAMANAN DAN PENEGAKAN HUKUM MALUKU PAPUA - Adrianus Mosa; Balthasar Watunglawar; Muhammad Husni Arifin (SOSCIED, 2022)
The purpose of this paper is to describe and analyze the influence of Leadership and , Communication on Employee performance. To achieve these objectives, this study uses quantitative research methods. Data were collected through questionnaires and documentation of 30 respondents analyzed using SPSS 22. The results showed that there was a significant influence between leadership, communication on employee performance. So to improve employee performance, the organization and institutional management must pay attention to improving good leadership and communication. The findings of this study are expected to be useful for further researchers in the fields of management, accounting, administration and economics.